Composite Materials: Effect of Constituent Materials on Composite Performance: Exploring Design Strategies via Machine Learning (Adv. Theory Simul. 6/2019). Issue 6 (4th June 2019) - Chen, Chun‐Teh; Gu, Grace X.
Abstract : With an integration of finite element method, molecular dynamics, and machine learning, this work highlights an interdisciplinary approach to investigate the effect of constituent materials on the behavior of composites including graphene nanocomposites. More details can be found in article number1900056 by Chun‐Teh Chen and Grace X. Gu.